THE EFFECT OF SPEED IN PROVIDING SERVICE, SERVICE OFFICER ABILITY AND QUALITY OF FACILITIES AND INFRASTRUCTURE ON PUBLIC SATISFACTION AT THE BELIAN VILLAGE OFFICE, BATAM DISTRICT, BATAM CITY - Sri Marlinawati; Sabri; Sumardin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the effect of Service Delivery Speed, Service Officers' Competence, and Quality of Facilities and Infrastructure on Community Satisfaction at the Belian Village Office, Batam Kota District, Batam City. This research employed a quantitative method with a sample of 100 respondents determined using the Slovin formula and Simple Random Sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS.The validity test results indicate that all items are valid (r-count > 0.197; sig < 0.05) and reliable with Cronbach's Alpha > 0.60 (X₁ = 0.916; Simultaneously, the three variables have a significant effect on Community Satisfaction with an F-value of 36.663 > 2.61 and a significance of 0.000 < 0.05, and an R² value of 0.534, meaning that 53.4% ​​of the variation in community satisfaction can be explained by the research model. Partially, Service Delivery Speed ​​(t = 2.253; sig 0.026), Service Officers' Competence (t = 10.349; sig 0.000), and Quality of Facilities and Infrastructure (t = 3.761; sig 0.000) have a positive and significant effect on Community Satisfaction. The most dominant variable is Service Officers' Competence (Beta = 0.785).